ELECTRODIAGNOSTIC STUDY IN HEALTHY SUBJECTS AND PATIENTS OF MOTOR NEUROPATHY OF UPPER AND LOWER LIMBS - Bano, Husan; Rukhsana, Nighat; Mannan, Fatima; Mannan, Abdul (Pakistan Journal of Physiology, 2013)
Background: A nerve conduction velocity test measures how quickly electrical impulses move along a nerve in order to exclude or detect muscle disorders. The objective of this study was to study the pattern of electrophysiological variables in motor nerves for detection of neuropathy. Methods: This experimental study was carried out in the Department of Physical Medicine and Rehabilitation, Jinnah Postgraduate Medical Centre, Karachi from Dec 2010 to Aug 2011. Patients of motor neuropathy (n=30) and normal healthy subjects (n=18) were included. The nerve action potential of normal subjects and patients were recorded with electromyography (EMG). Motor nerve conduction velocity (NCV) and other variables such as proximal latency (PL), distal latency (DL), conduction time (CT), and amplitude of motor action potential (MAP) recorded in median, Ulnar nerves of upper limb and posterior tibial, common peroneal nerves of lower limb by given supra-maximal stimulus of 200–250 volts for duration of 0.2 mSec (6 times higher than motor threshold). Data were analysed statistically on SPSS-17. Results: Slow nerve conduction velocity, reduced amplitude of motor action potential and prolong distal latencies in median, ulnar, posterior tibial and common peroneal nerves observed in neuropathic patients. The PL, DL, CT were significantly increased (p<0.01), where as NCV and MAP significantly reduced in all cases of motor neuropathy (p<0.01). Conclusion: The study results proved that electrophysiological examination using EMG/NCV is the valuable electro-diagnostic test for early diagnosis of abnormal functions of nerve and its appropriate disorders. Pak J Physiol 2013;9(2):8–10